An Aboriginal and Torres Strait Islander Voice to Parliament: what can Australia learn from other countries? (Commonwealth Journal of Local Governance, 2023)
This is an edited version of a presentation to the Australian Institute for International Affairs on 16 May 2023. The authors explain the origins of the proposal for an Aboriginal and Torres Strait Islander Voice to the Australian Parliament and why the Voice should be enshrined in the Australian Constitution. They also compare how other countries ensure that Indigenous peoples’ interests are properly considered in the processes of government. They conclude by noting that the proposed Voice is a modest request by Aboriginal and Torres Strait Islanders to be seen in the Constitution and heard in the democratic life of Australia.